2021
DOI: 10.1177/19485506211018132
|View full text |Cite
|
Sign up to set email alerts
|

Linking Self-Reported Social Distancing to Real-World Behavior During the COVID-19 Pandemic

Abstract: In an effort to combat COVID-19 and future pandemics, researchers have attempted to identify the factors underlying social distancing. Yet, much of this research relies on self-report measures. In two studies, we examine whether self-reported social distancing predicts objective distancing behavior. In Study 1, individuals’ self-reported social distancing predicted decreased mobility (assessed via smartphone step counts) during the COVID-19 pandemic. While participants high in self-reported distancing (+1 SD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 49 publications
2
42
0
1
Order By: Relevance
“…That said, we still have confidence in the validity of our self-report data given that (a) we found that associations between lockdown compliance and personality traits persisted even after controlling for social desirability, (b) lockdown compliance was highly correlated with self-reported distancing behavior, and (c) the extent to which self-reported compliance is biased appears to be small (see A. Gollwitzer, McLoughlin et al, 2021;Larsen et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…That said, we still have confidence in the validity of our self-report data given that (a) we found that associations between lockdown compliance and personality traits persisted even after controlling for social desirability, (b) lockdown compliance was highly correlated with self-reported distancing behavior, and (c) the extent to which self-reported compliance is biased appears to be small (see A. Gollwitzer, McLoughlin et al, 2021;Larsen et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…Third, as in most previous studies, adherence measurements were self-reported. Future studies should confirm the results with more objective measures of actual preventive behaviour (e.g., Gollwitzer et al, 2021).…”
Section: Limitations and Outlookmentioning
confidence: 82%
“…Future work should focus on disentangling whether specific elements of the messages are particularly effective at promoting social distancing. Third, policymakers and public health experts had repeatedly emphasized the importance of social distancing and survey respondents may have over-reported their intentions to social distance due to social desirability concerns, though past work has found that reported behavioral intentions correlate with actual behavior [ 68 ] and people’s self-reported behavior is not affected by social desirability bias [ 69 ]. Third, as the COVID-19 pandemic has rapidly evolved and different behaviors, like masking or vaccination, have become more salient in public discourse, the messages that we find to be effective in summer 2020 may not be as effective as the pandemic has progressed.…”
Section: Discussionmentioning
confidence: 99%